An optimized hepatocellular carcinoma prediction model for chronic hepatitis B with well‐controlled viremia. (22nd April 2020) - Lee, Hye W.; Park, Soo Y.; Lee, Myeongjee; Lee, Eun J.; Lee, Jinae; Kim, Seung U.; Park, Jun Y.; Kim, Do Y.; Ahn, Sang H.; Kim, Beom K.
Abstract: Background and Aims: Hepatocellular carcinoma (HCC) risk in chronic hepatitis B (CHB) substantially decreased in the era of potent antiviral therapy. We developed an optimized HCC risk prediction model for CHB with well‐controlled viremia by nucelos(t)ide analogs (NUCs). Method: We analysed those who achieved virological response (VR; serum HBV‐DNA < 2000 IU/mL on two consecutive assessments) by NUCs. Liver stiffness by transient elastography, ultrasonography and laboratory tests was performed at the time of confirmed VR. Patients with decompensated cirrhosis or HCC at baseline were excluded. Multivariate Cox‐regression analysis was used to determine key variables to construct a novel risk‐scoring model. Results: Among 1511 patients, 9.5% developed HCC. C irrhosis on ultrasonography (adjusted HR [aHR] 2.47), a ge (aHR 1.04), m ale (aHR 1.90), p latelet count <135 000/uL (aHR 1.57), a lbumin <4.5 g/dL (aHR 1.77) and liver s tiffness ≥11 kPa (aHR 6.09) were independently associated with HCC. Using these, CAMPAS model was developed with c‐index of 0.874. The predicted and observed HCC probabilities were calibrated with a reliable agreement. Such results were reproduced from internal validation and external validation among the independent cohort (n = 252). The intermediate‐risk (CAMPAS model score 75 ~ 161) and high‐risk (score >161) groups were more likely to develop HCC compared with the low‐risk group (score ≤75) with statistical significances (HRs; 4.43 and 47.693 respectively; both P  < .001). Conclusion: CAMPAS model derived through comprehensive clinical evaluation of liver disease allowed the more delicate HCC prediction for CHB patients with well‐controlled viremia by NUCs.